Efficient ternary organic photovoltaics with two polymer donors by minimizing energy loss. Issue 3 (19th December 2019) - Ma, Xiaoling; An, Qiaoshi; Ibraikulov, Olzhas A.; Lévêque, Patrick; Heiser, Thomas; Leclerc, Nicolas; Zhang, Xiaoli; Zhang, Fujun
Abstract : Energy loss is decreased by employing a ternary strategy, which should be an efficient approach to improve the performance of OPVs. Abstract : Efficient ternary organic photovoltaics (OPVs) are fabricated with two polymer materials PF2 and J71 as donors and Y6 as the acceptor. The PF2 and J71 based binary OPVs exhibit 10.26% and 9.56% power conversion efficiency (PCE), respectively. Even with similar highest occupied molecular orbital (HOMO) energy levels of PF2 and J71, the J71 based binary OPVs show a relatively high open circuit voltage ( V OC ) of 0.86 V compared with 0.71 V for PF2 based binary OPVs. The V OC s of ternary OPVs monotonously increased with the increase of J71 content in donors, which should be mainly ascribed to the reduced energy loss according to the V OC s of two binary OPVs and the HOMO energy levels of two donors. The short circuit current density ( J SC ) and fill factor (FF) of ternary OPVs can also be simultaneously enhanced with the J71 content up to 30 wt% in donors, leading to 12.12% PCE of the optimized ternary OPVs with a J SC of 24.97 mA cm −2, a FF of 64.70% and a V OC of 0.75 V. Reducing energy loss by the ternary strategy is rarely reported in the literature, which should also be an efficient method to realize performance improvement of OPVs.